RANSOM ANDTHE FUGITIVE MOVEMENT: Break and Continuity - AGGABOU, Zouaoui (Journal of Human Sciences, 2008)
Abstract:     The purpose of this paper is to put forward the argument that there exits a clear and logical relationship between the Fugitive-Agrarian movements and New Criticism.  This relationship is determined by the sum of beliefs and attitudes that the major Agrarians, namely John Crowe Ransom, Donald Davidson and Allen Tate shared and defended either collectively or individually.  In so far as these beliefs express a reaction against the modern world, with at the background the drastic changes that were taking place in the American South in the 1930’s, they represent an “ideology”.  What should therefore emerge from this study is that the joint adventure of these writers finds its essential unity in the dominant theory of Agrarianism.  Such an intention invites a consideration of the historical and cultural contexts that made a group of Southern writers become respectively, Fugitive Poets, Southern Agrarians, and, finally, New Critics whose views and multifaceted inquiries constitute an important contribution to the Southern Literary Renaissance.